Enhancing International Buyer-Seller Relationship Quality and Long-Term Orientation Using Emotional Intelligence: The Moderating Role of Foreign Culture - Leonidou, Leonidas C.; Aykol, Bilge; Larimo, Jorma; Kyrgidou, Lida P.; Christodoulides, Paul (My University, 2021)
Building on Emotion Regulation Theory, we examine the role of an exporter’s emotional intelligence (EI) in enhancing the quality and boosting the long-term orientation of the working relationship with its import buyers. Using data gathered from 262 Greek exporters, we confirm that the proper use of EI helps to improve trust, commitment, cooperation, and satisfaction in the relationship with their importers, which subsequently contribute to its long-term orientation. This favorable effect of EI on relationship quality dimensions is amplified when exporters deal with importers located in countries with cultures characterized by low power distance, low individualism, low masculinity, high uncertainty avoidance, and high (national) long-term orientation.
Keywords: Buyer–seller relationships; Culture; Emotional intelligence; Exporting